Transformasi Modal Sosial ke Modal Ekonomi dalam Acara Rasulan di Kalurahan Kemiri Kapanewon Tanjungsari Kabupaten Gunungkidul - Mohamad Firdaus (Jurnal Masyarakat dan Desa, 2021)
This study will discuss and explore the transformation of social capital into economic capital formed in Kemiri Village, Kapanewon Tanjungsari, Gunungkidul Regency. Rasulan is a form of social capital of the Kemiri community which has been formed since the ancestors and its existence and sustainability are always maintained. The form of social capital, which began with the Rasulan event, is the main capital of the Kemiri Village community in maintaining the habit of mutual cooperation. Coleman embeds his concept of social capital in the context of rational choice theory. Social interdependence arises between actors, as they are attracted to events and resources controlled by other actors to maximize their utility by rationally choosing the best solution for them. Furthermore, the maximum utility found in the Kemiri community, one of which is the management of Sogo Lake for Jathilan arts and building rentals in each hamlet. With the maximum utility as mentioned earlier, it can be understood that there was a transformation that was originally present on the organization of the Rasulan event as a social model into economic capital that could be utilized by the people of Kemiri Village.